A study on hunting activity of Sambar deer and Bearded pig in Paitan Forest Reserve, Pitas, Sabah, Malaysia - Anna Wong; Yong, Huaimei; Christopher Wong; Jumrafiah Abd. Shukor (Penerbit UMS, 2012)
This paper presents hunting activities in Paitan, Sabah, especially of Sambar deer (Cervus unicolor) and Bearded pig (Sus barbatus) through interviews with communities and analysis of hunting licenses issued by the Sabah Wildlife Department (SWD). The hunting activity was found to have a very close relation to the culture of the local people in Paitan; it provides not only monetary support but also recreational and social values. Hunting was mostly carried out by spearing and hunting dogs, followed by firearms, snares and blowpipes. From data obtained from SWD, there was a gradual decline in the number of licenses issued in Paitan. This situation may be due to the decline in the population of Sambar deer and Bearded pigs in Paitan Forest Reserve. Thus, the issuance of the hunting license on both the animals should be reduced in order to maintain the current population status of Sambar deer and Bearded pig. The result also shows that there is significant difference in the number of hunting licenses issued on a monthly basis for Bearded pig but not for Sambar deer.